PERANG TARIF DALAM INDUSTRI LAYANAN JASA TELEPON SELULER: ANALISIS WACANA IKLAN OPERATOR TELEPON SELULER DI MEDIA MASSA - Syamsi, Kastam (Diksi, 2009)
As a product of media, advertisements in both print and electronic media withtheir hegemony are made to persuade readers or listeners to act as the advertisements wish,namely buying the advertised products. Based on an analysis of mass media, inadvertisements by cellular phone operators, there is a price war as a strategy to attractconsumers. Each cellular phone operator tries to show an image that the company offersthe lowest price. This may influence and deceive consumers as the party that is forced touse the company's service. In practice, an offer with a low price usually needs a conditionand requirement that consumers have not known before. Therefore, it is necessary thatconsumers should be selective and critical in digesting an advertisement made by a cellularphone operator offering a low price.Keywords: advertisement, cellular phone operator, mass media